The Martin Luther of Islam? Ismail al-Faruqi’s Impact on Contemporary Islamic Intellectualism (American Journal of Islam and Society, 2014)
Although I did not study under Isma’il al-Faruqi (d. 1986) directly as didscholars like John Esposito and many others, I have, nonetheless, had thepleasure of teaching and introducing my students to his person and ideas forthe past decade. His former students have convened two conferences (London[2010] and Kuala Lumpur [2013]) to celebrate his intellectual contribution,from which came a book and a special issue of this journal. Could all of thisbe sentimental hero worship, or a life worthy of sincere celebration and emulation?Studying his intellectual publications and tracing his academic andsocial activities make it abundantly clear that he was unique and committedto improving the lot of Islam and Muslims.John Esposito and John Voll narrate in their Makers of ContemporaryIslam a brief story: “An old Christian acquaintance of al-Faruqi once commentedthat al-Faruqi believed that Islam was in need of reformation and, hebelieved, al-Faruqi aspired to be its Luther.”1 Even though this was a sincereassessment, Esposito and Voll speculate that al-Faruqi would have preferredthe word mujāhid. Esposito prefers to use this term to describe al-Faruqi, ashe did in his “Memoirs of a Scholar and a Mujahid.”2 Although al-Faruqinever referred to himself in this way, portraying him as Islam’s Martin Lutherdoes have some significance to contemporary Islam and Islamic thought.Luther appeared on the Christian intellectual and religious scene duringthe 1500s, a time when Christian theology and thought were perceived as profoundlycorrupt. There were indulgences, essentially “get out of purgatoryfree” cards, that only the rich and powerful could afford. Championed bypopes and princes, this practice undermined the Christian’s role of personalresponsibility and Jesus’ message (peace be upon him).Church leaders sought to monopolize religious knowledge by prohibitingtranslations of the Bible and to stifle the pursuit of knowledge by publishingtheir Index of Forbidden Books (from 1559 to 1966, when Pope Paul VI abolishedit). The church hierarchy also began teaching that following the Bible ...